Topografias afetivas na ficção de Chico Buarque - Borowski, Gabriel (Studia Romanica Posnaniensia, 2019)
This text is an attempt to discuss the affective dimension of the experience of the city in three novels by the Brazilian writer and composer Chico Buarque. In Estorvo (1991) the protagonist is unable to create bonds with the urban space and his perception of the city is a blend of actual observation and his delirious subjectivity. In Budapeste (2004) the main character is experiencing the capital of Hungary as an affective representation of the actual place. In Leite derramado (2009) the narrator is organising his story through affective memories of significant places.